Konsep Sustainable Development (Pembangunan Berkelanjutan) Berbasis Sosial Dan Ekonomi Terhadap Perlindungan Sumber Daya Alam Perspektif Maqashid Syariah - Nurbaiti, Nurbaiti; Armayani Hasibuan, Reni Ria; Siregar, Syifa Nabilla (Jurnal Manajemen Akuntansi (JUMSI), 2024)
Sustainable development based on natural resources that do not pay attention to aspects of environmental sustainability will ultimately have a negative impact on the environment itself. Because basically natural resources and the environment have a limited carrying capacity. In other words, economic development that does not pay attention to the capacity of Natural Resources and the environment will lead to development problems in the future. This study aims to analyze the protection of Natural Resources in the city of Tanjungbalai from the social and economic side for Sustainable Development. In this study the method used is a qualitative method and the data is processed using software Nvivo 12 plus. The results showed that the people of Tanjungbalai City have implemented the concept of sustainable development to maintain and preserve marine ecosystems, and some people also understand about working according to Islamic principles of maqashid Sharia, namely maintaining religion, maintaining the soul, maintaining reason, preserving property, and preserving offspring.